THE EFFECT OF NUTRITION EDUCATION USING CARDS AND VIDEOS ON FRUITS AND VEGETABLES KNOWLEDGE - Ibnu Malkan Bakhrul Ilmi; Gendis Fathia Fajarina (Universitas Darussalam Gontor, 2023)
Background: Based on the results of the 2018 Riskesdas report, approximately 95.5% of the Indonesian population has insufficient consumption of vegetables/fruits. The impact of inadequate fruit and vegetable consumption can lead to several nutritional problems, such as obesity in schoolchildren and digestive disorders. One of the efforts that can be made to provide information related to fruits and vegetables is through educational interventions. Objective: To determine the influence of nutrition education using card games and animated videos on the knowledge of fruits and vegetables among school-aged children at Balekambang 01 Pagi Elementary School. Method: The research design used was a quasi-experimental design with a pre-post test group design involving 124 students from grades III, IV, and V selected through stratified random sampling technique. Data were analyzed using the Wilcoxon and Mann Whitney tests. Result: There were differences in the pre-post test knowledge of the respondents regarding nutrition education using card game media (p = 0.000) and animated video media (p = 0.000). There was no significant difference in the knowledge improvement between the two media, as indicated by a p-value of 0.221 (p-value > 0.05). Conclusion: There is an influence of nutrition education using card games and animated videos on the knowledge of fruits and vegetables among students at Balekambang 01 Morning Elementary School. Keywords: Fruits and Vegetables, Nutrition Education, Card Games, Animated Videos